In Prakriti: Feminocentric form. Issue 1 (1st April 2017) - Hamilton, Mark James
This article offers new perspectives on the complex discourse – in publication and international conversation – debating the ways in which women are represented through contemporary performances of bharatanatyam through the lens of the author's life as a white queer man dancing the form. There are contested histories of bharatanatyam that chart the metamorphosis of occult Dravidian temple worship practices and mediaeval court entertainments into a transnational embodiment of Indian women, important to the Indian state and the continuing colonialist forces it contains. This article considers how secularist and sectionalist readings of cultural practices prohibit our understanding of the radical ontology that underpins bharatanatyam, and consequently the reach of its transformative power. Significantly, such ontology potentially involves the absorption of men in a feminocentric Weltanschauung. On an immediate level (comparable to discussions about other theatrical idioms) this is because of the overlap between the performative construction of femininity and the representational performance of femininity embedded and intertwined in bharatanatyam. On a more unique level, it is also because the cosmology underpinning bharatanatyam perceives all material existence as divinely female – as Prakriti.